2016
DOI: 10.1007/s11682-016-9529-2
|View full text |Cite
|
Sign up to set email alerts
|

Reduced volume of gray matter in patients with trigeminal neuralgia

Abstract: Accumulating evidence from brain structural imaging studies has supported that chronic pain could induce changes in brain gray matter volume. However, few studies have focused on the gray matter alterations of Trigeminal neuralgia (TN). In this study, twenty-eight TN patients (thirteen females; mean age, 45.86 years ±11.17) and 28 healthy controls (HC; thirteen females; mean age, 44.89 years ±7.67) were included. Using voxel-based morphometry (VBM), we detected abnormalities in gray matter volume in the TN pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 36 publications
5
49
0
Order By: Relevance
“…Protracted pain can cause changes in the brain structure (Kuchinad et al, 2007; Li et al, 2016), and the underlying mechanism may be explained by neuronal plasticity (Woolf and Salter, 2000). Our data revealed that the MK values in the right ACC were significantly negatively correlated with pain duration and VAS scores, whereas the AK values in the right mPFC were significantly negatively correlated with the VAS scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protracted pain can cause changes in the brain structure (Kuchinad et al, 2007; Li et al, 2016), and the underlying mechanism may be explained by neuronal plasticity (Woolf and Salter, 2000). Our data revealed that the MK values in the right ACC were significantly negatively correlated with pain duration and VAS scores, whereas the AK values in the right mPFC were significantly negatively correlated with the VAS scores.…”
Section: Discussionmentioning
confidence: 99%
“…The brain gray matter is closely associated with the body’s pain perception (Cauda et al, 2014; Emerson et al, 2014). A large body of evidence indicated that the gray matter might exhibit abnormalities under chronic pain status, such as trigeminal neuralgia (Obermann et al, 2013; Li et al, 2016), chronic low back pain (Seminowicz et al, 2011; Fritz et al, 2016), fibromyalgia (Hsu et al, 2009; Robinson et al, 2011), phantom limb pain (Preissler et al, 2013), cyclic menstrual pain (Tu et al, 2010), complex regional pain syndrome (Geha et al, 2008), and migraine (Magon et al, 2015). In addition, the density and volume changes of gray matter in patients with chronic pain are also related to clinical traits (Apkarian et al, 2004; Kuchinad et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Pain was identified as a psychological stress 30 and, vice versa, stress is a factor that causes and maintains pain intensity 29 . Several studies have shown morphological as well as functional changes in both neuralgic 1,3,[5][6][7][8] and stress states [11][12][13][14] . We noticed that latencies at the neuralgic side were shorter as a result of the hyper-excitability of dysfunctional nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Demyelination may give an increase to electrical hyper excitability, spontaneous and triggered ectopic impulses and cross excitation among neighboring afferents 1,3,5 . Atrophy of the trigeminal nerve 6,7 and reduced volume of gray matter 1,8 are also seen.…”
Section: Introductionmentioning
confidence: 99%
“…In several trigeminal neuralgia studies, the reduction of the volume of the anterior cingulate cortex (ACC) and the increase of the volume of the temporal cortex were found. Li et al also considered that the increase in the volume of the upper and middle gyrus was proportional to the duration of trigeminal neuralgia [6,7].…”
Section: Vbmmentioning
confidence: 99%